STUDY OF EDUCATIONAL ACHIEVEMENT OF SECONDARY SCHOOL STUDENTS - Singh, Shweta; Pandey, Narendra (International Journal of Research -GRANTHAALAYAH, 2025)
The study of educational achievement of secondary school students in Gaya district of Bihar is an important effort towards understanding the current educational system and performance of students. Gaya district, which is one of the major historical and educational centers of Bihar, has a constantly increasing participation of boys and girls in secondary education here. To know the comparison of educational achievement of boys and girls studying at secondary level, the presented research work was conducted on 200 students, 100 boys and 100 girls of class 9 and 10. Many points of comparison were considered such as gender and educational achievement of rural and urban boys and girls, etc. have been studied.